Модернізація сепаратора СЦ-3 - Дідур, В. В.; Петриченко, Є. А.; Дашивець, Галина Іванівна; Didur, V.; Petrychenko, I.; Dashyvets, Galyna (Запоріжжя : ТДАТУ, 2024)
UA: Виробництво рослинних олій у сільськогосподарських підприємствах стримується відсутністю недорогого малогабаритного обладнання, що забезпечує випуск продукції, яка відповідає міжнародним стандартам якості. Розробка економічного недорогого вітчизняного обладнання та організація його виготовлення є актуальними. Результати аналізу інформаційних джерел доводять можливість якісного очищення рослинних олій в умовах сільськогосподарських підприємств на вертикальних конічних центрифугах при використанні природного фільтруючого матеріалу – мінералу цеоліту. В даній роботі розглядається можливість модернізації сепаратора СЦ-3 Представлено розроблену схему барабана експериментальної центрифуги. Представлено принципову схема модернізації центрифуги СЦ-3, загальний вид переобладнаної центрифуги. Описано принцип роботи модернізованої центрифуги. Встановлено, що модернізація сепаратора СЦ-3 у конічну фільтруючу центрифугу з цеолітовою фільтрувальною перегородкою можлива без істотних конструктивних змін, що дозволить виробникам сепараторів СЦ-3 підвищити ринок збуту та конкурентоспроможність своєї продукції. EN: The production of vegetable oils in agricultural enterprises is held back by the lack of inexpensive, small-sized equipment that ensures the production of products that meet international quality standards. The development of economical, inexpensive domestic equipment and the organization of its production are relevant. The results of the analysis of information sources prove the possibility of high-quality purification of vegetable oils in the conditions of agricultural enterprises on vertical conical centrifuges when using a natural filter material - the mineral zeolite. This work considers the possibility of modernizing the CЦ-3 separator (which is produced in series and is intended for cleaning the oil of marine engines) for its use in the cleaning of vegetable oils. Examples of the use of oil production waste in various branches of production are described - in the food industry, in the manufacture of fodder for cattle. Technical phosphatides are used in the textile and leather industry, where they are used to impregnate fabrics, wool and leather in order to increase its elasticity. They are also introduced into the composition of varnishes and paints in order to increase the depth of their shades. The work presents methods of cleaning oils from phosphatides that are hydrated and from those that are not hydrated. The developed scheme of the drum of the experimental centrifuge is presented and the research of filtering conical centrifuges is carried out on the basis of the developed methodological base and the theory of centrifugation. The principle of operation of the laboratory installation is described. The plant performance equation is provided. The schematic diagram of the modernization of the CЦ-3 centrifuge, the general view of the converted centrifuge, is presented. The principle of operation of the modernized centrifuge is described. It was established that the modernization of the CЦ-3 separator into a conical filter centrifuge with a zeolite filter partition is possible without significant structural changes, which will allow the manufacturers of CЦ-3 separators to increase the sales market and the competitiveness of their products.
Modernization of the CЦ -3 separator
Keywords: рослинні олії; актуальність; центрифугування; фільтрувальна перегородка; цеоліт; властивості; Сокирніт; теорія; переобладнання; сепаратор; пристрій; vegetable oils; topicality; centrifugation; filtering membrane; zeolite; properties; Sokirnit zeolite; theory; re-equipment; separator; design